Different types of flooring and space allowance in heavy pigs: effects on growth performances - G. Pastorelli; R. Rossi; C. Corino (Italian Journal of Animal Science, 2011)
The pig’s body size dimensions are the primary determinant of its static space requirement. This is important from the welfare point of view since an animal needs a minimum amount of space to perform a certain behaviour pattern and if the space is not allowed, a risk of abnormal behaviours and reduction on performance must be expected (Petherick 1983). As it is also important the flooring types influencing animal welfare and health too...